Early efficacy of postoperative rehabilitation training for lumbar disc herniation - Yuwei Zhu; Shuang Xia; Weihang Yang; Fengchao Shi; Hongjian Ji (BMC, 2023)
Abstract Objective To investigate the early clinical efficacy of rehabilitation training after unilateral biportal endoscopy for lumbar disc herniation and to analyze the prognostic factors. Methods A total of 100 patients with lumbar disc herniation who underwent unilateral biportal endoscopy at The Sixth Affiliated Hospital of Nantong University from January 2019 to January 2021 were retrospectively analyzed. The control group was given a standard home-based exercise program, while the intervention group was given a substituted rehabilitation training opposed to a standard home-based exercise program. The early postoperative pain relief and quality of life values were compared between the two groups, and the independent risk factors affecting the prognosis of patients were analyzed. Results There were no significant differences in sex, age, smoking, drinking, BMI, course of disease, type of disc herniation, preoperative VAS, ODI or SF-36 between the two groups (P > 0.05). There was no significant difference in preoperative and postoperative VAS and ODI scores at 3 months between the two groups (P > 0.05), yet there were significant differences in postoperative VAS and ODI at 12 months (P < 0.05). The SF-36 score of the intervention group was lower than that of the control group at 12 months, and the difference was statistically significant (P < 0.05). The excellent rate of the Macnab standard modification used in the intervention group was 88.00% at 12 months, and that in the control group was 62.00%. The difference between the two groups was considered to indicate a statistically significant (P < 0.05). The results of logistic multivariate regression model analysis showed that rehabilitation training (95% CI: 1.360-12.122, P = 0.012), the type of intervertebral disc (95% CI: 0.010-0.676, P = 0.020), and age (95% CI: 1.056-8.244, P = 0.039) were independent risk factors affecting the prognosis of patients. Conclusion Postoperative rehabilitation training can effectively relieve pain and improve quality of life; thus, it is highly recommended in the clinic. Postoperative rehabilitation training, intervertebral disc type and age are independent risk factors for the postoperative prognosis of lumbar intervertebral disc herniation.